Biblical Bestiary: Ibex (Biblical archaeology review, 2023)
The article focuses on the ibex, a species of wild goat found in mountainous regions, discussing its various types, appearances in ancient art, mentions in the Hebrew Bible, and its cultural significance in different contexts. It also explores the ibex's symbolism and associations, including its role in Jewish dietary laws and as a personal name in biblical narratives.